The Idea of Target Costing. Identification Of Environmental Characteristics of The Product - Case Study - CHALASTRA MICHAŁ; SIEMIONEK-LEPCZYNSKA ANNA (Communications of International Proceedings, 2024)
One of the elements of target costing is identifying the desired features of a product. According to this concept, a product should possess only useful features, which are those accepted by buyers. This acceptance is reflected in their willingness to pay a higher price for the addition of such features. Features that are not desired by buyers, which are indifferent to them and do not interest them, should be removed from the product. Bearing the costs of producing or delivering these features is thus unjustified. According to the Lean Management concept, such features are considered waste because costs are incurred to produce unnecessary product features from the buyer's perspective. The aim of this paper was to present a case study conducted in Polish company. For each product, desired features must be established using market research. The same products may have different desired features in various geographic markets or among different buyer groups due to differences in climate, legal conditions, or buyer awareness.
Keywords: Target Costing; circular economy; green activities.